2019
DOI: 10.1111/jfpp.14012
|View full text |Cite
|
Sign up to set email alerts
|

Unripe plantain flour as a dietary fiber source in gluten‐free spaghetti with moderate glycemic index

Abstract: Gluten‐free products generally have low dietary fiber (DF) content. The aim of this study was to prepare a DF‐rich gluten‐free spaghetti and to evaluate the influence of the DF source on the chemical composition, cooking quality, texture, starch digestibility, and predicted glycemic index of the product. Unripe plantain flour (UPF) and Hi‐Maize 260 were used as DF sources. The total DF in the uncooked samples was higher in the spaghetti with Hi‐Maize 260 (17.4%) than in the UPF‐containing one (9.6%), but no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…RS2 increased more total dietary fibers than unripe plantain flour in uncooked spaghetti, while made similar performances in lowering GI, consequently transferring spaghetti into medium GI food. [ 141 ] It is strongly demonstrated that unripe plantain flour is an alternative dietary fiber to RS, and the similar functions were also found in chickpea, [ 142 ] cassava and banana flour. [ 143 ]…”
Section: Food Applicationmentioning
confidence: 97%
“…RS2 increased more total dietary fibers than unripe plantain flour in uncooked spaghetti, while made similar performances in lowering GI, consequently transferring spaghetti into medium GI food. [ 141 ] It is strongly demonstrated that unripe plantain flour is an alternative dietary fiber to RS, and the similar functions were also found in chickpea, [ 142 ] cassava and banana flour. [ 143 ]…”
Section: Food Applicationmentioning
confidence: 97%
“…Flours are also obtained from unripe plantain when quality parameters are not met for commercialization. [ 1 ] Those flours have been used in bakery products, [ 2 ] pasta, [ 3 ] snacks [ 4 ] and for ethanol production. [ 5 ] Nevertheless, the peel of plantain is discarded when producing commercial flours.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these conditions, overweight and obesity have been related to a deficient intake of dietary fiber in the diet (Magallanes‐Cruz et al, 2020). The Food and Agriculture Organization (FAO) has suggested a dietary fiber intake of 35 g/day; however, the average daily fiber intake worldwide is below that recommended by health agencies (15 g/day; Agama‐Acevedo et al, 2019). For this reason, recent research has shown that bread confers an optimal dietary matrix to incorporate bioactive compounds (Ballester‐Sánchez et al, 2019) to improve nutrient intake.…”
Section: Introductionmentioning
confidence: 99%